Probing the nucleoporin FG repeat network defines structural and functional features of the nuclear pore complex - Stelter, Philipp; Kunze, Ruth; Fischer, Jessica; Hurt, Ed (The journal of cell biology, 2011)
Unraveling the organization of the FG repeat meshwork that forms the active transport channel of the nuclear pore complex (NPC) is key to understanding the mechanism of nucleocytoplasmic transport. In this paper, we develop a tool to probe the FG repeat network in living cells by modifying FG nucleoporins (Nups) with a binding motif (engineered dynein light chain-interacting domain) that can drag several copies of an interfering protein, Dyn2, into the FG network to plug the pore and stop nucleocytoplasmic transport. Our method allows us to specifically probe FG Nups in vivo, which provides insight into the organization and function of the NPC transport channel.
Gesehen am 21.10.2022